Effects of trammel net mesh size on fish stocks and fishing productivity: evidence from small scale artisanal fisheries in Southern Ionian Sea - Baan, Dorian (2014)
Recent publications have shown that a considerable proportion of the landings in theMediterranean are constituted of illegal individuals with length below their minimum landing size(MCRS, former MLS) and of even more immature individuals that have not reached their length atfirst maturity (L) and thus were not able to spawn even once, stressing the inadequacy of the actualfisheries management measures applying in the Mediterranean and their unefficiency to protect thefish stocks. In this study, the ecological and economical effects of 4 different inner panel mesh sizesof trammel nets in artisanal fisheries in Zakynthos island (Ionian Sea, Greece) were investigated.The length compositions of the landings were thus compared to Lm and MCRS with respect to thedifferent mesh sizes, and differences in catch rate, income and species compostition were alsotested. The high percentages of individuals under Lmm in every mesh sizes indicated that the stocksare facing a strong growth overfishing and that the current management measures are not able tomaintain the stocks at a sustainable level. We also demonstrated that the 21mm mesh size showedsignificantly higher percentage of undersized individuals than every other mesh sizes, andsignificantly lower catch rate and income. This mesh size should thus be bannished from thefisheries if we are to set management plans that are both ecologically and economically sustainable.Our findings should finally help setting up future management plans for the MPA of the NationalMarine Park of Zakynthos, that aim to be ecologically and socio-economically sustainable, througha combination of efficient and meaningful technical measures and ecosystem-based approaches.